Hermeneutika Hadis Menurut Muhammad Iqbal: Kajian Teoretis dan Implikasinya pada Era Kontemporer - Adnan; Musahadi; Nisrin Mu'azzaz (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2026)
This study explores Muhammad Iqbal’s philosophical contribution to Hadith hermeneutics through his synthesis of tradition and modernity. Iqbal views the Hadith as a living tradition that engages with human reason and social transformation rather than a static legal text. His thought emphasizes the unity of sanad and matn, the dynamic principle of ijtihad, and the balance between spiritual authenticity and contextual relevance. Drawing on "The Reconstruction of Religious Thought in Islam", this research proposes an Iqbal-inspired hermeneutical model comprising four stages: normative–dynamic reading, historical–sociological contextualization, sanad–matn synthesis, and contextual ijtihad application. The framework reorients Hadith studies toward a dialogical and transformative approach that integrates fidelity to revelation with responsiveness to modern intellectual challenges, positioning Iqbal’s hermeneutics as both a theoretical paradigm and a practical guide for revitalizing prophetic teachings in contemporary Muslim life.